问题 解答题
下面各题怎样简便怎样算.
3
4
-(
5
6
-
1
2
)+
2
3
1
7
+
5
6
+
6
7
10
11
-(
1
4
-
1
11
)
4
7
+
6
7
-
3
4
-
1
4
2
3
-
1
6
+
1
3
2-
4
7
+
2
9
-
3
7
答案

(1)

3
4
-(
5
6
-
1
2
)+
2
3

=

3
4
-
1
3
+
2
3

=

3
4
+(
2
3
-
1
3
),

=

3
4
+
1
3

=

13
12

(2)

1
7
+
5
6
+
6
7

=(

1
7
+
6
7
)+
5
6

=1+

5
6

=1

5
6

(3)

10
11
-(
1
4
-
1
11
),

=

10
11
-
1
4
+
1
11

=

10
11
+
1
11
-
1
4

=1-

1
4

=

3
4

(4)

4
7
+
6
7
-
1
4
-
3
4

=(

4
7
+
6
7
)-(
1
4
+
3
4
),

=

10
7
-1,

=

3
7

(5)

2
3
-
1
6
+
1
3

=(

2
3
+
1
3
)-
1
6

=1-

1
6

=

5
6

(6)2-

4
7
+
2
9
-
3
7

=(2+

2
9
)-(
4
7
+
3
7
),

=2

2
9
-1,

=1

2
9

单项选择题
单项选择题